Transformations of policing - Henry, Alistair; Smith, David J. (The Edinburgh Centre of Law and Society, 2007)
Looking back on Police and people in London / Alistair Henry -- The trajectory of "private policing" / Les Johnston -- Police ethnography in the house of serious and organized crime / James Sheptycki -- Policing ethnic minorities / Alistair Henry -- Public order: then and now / P.A.J. Waddington -- "Reassurance policing: feeling is believing" / Adam Crawford -- The architecture of policing: towards a new theoretical model of the role of constraint-based compliance in policing / Richard Jones -- Policing London: twenty years on / Mike Hough -- Managing the police through a time of change / Peter Neyroud -- The future of policing in Britain / Tim Newburn -- Policing our future / Clifford Shearing -- New challenges to police legitimacy / David J. Smith -- Index